The Role of Financial Technology in Improving Performance in Jordanian Islamic Banks - Raed Hendawi; Nehad Ibrahim Abd Alfatah Ineizeh; Obada Jebreen Hussein; Mohammad Alkahtani (Creative Publishing House, 2024)
Indexed by Scopus